Development and results of a questionnaire to measure carer satisfaction after stroke. Issue 6 (December 1993) - Pound, P; Gompertz, P; Ebrahim, S
Abstract : STUDY OBJECTIVE--To develop a carer satisfaction questionnaire for use as an outcome measure in stroke, to test the measure for reliability and validity, and to survey levels of carer satisfaction with services for stroke patients. DESIGN--Postal survey of carer satisfaction with stroke services was carried out using the questionnaire we developed and tested. Internal consistency was tested and construct validation was explored by examining correlations with other outcome measures (the Faces Scale, the Nottingham Health Profile, the short form of the Geriatric Depression Scale, and the patient's Barthel Index score). SETTING--Two adjacent districts in North East Thames Regional Health Authority. PARTICIPANTS--A total of 103 carers were identified from 219 people who had survived a stroke to six months. During the pilot stage, six of seven carers who were invited to participate in in depth interviews and 15 of 23 carers (65%) who were invited to completed the first draft of the questionnaire. MAIN RESULTS--The questionnaire was divided into two sections, one on inpatient services (Carer Hospsat) and one on services after discharge (Carer Homesat). The questionnaire had construct validity, providing significant correlations with the Faces Scale (Carer Hospsat r = 0.59, p < 0.00001 and Carer Homesat r = 0.68, p < 0.00001), the patients' Barthel score (Carer Hospsat r = 0.25, p = 0.01), and the patients' Nottingham extended Activities of Daily Living (ADL) scale (Carer Hospsat r = 0.31, p = 0.002). Internal consistency was high for both sections (Cronbach's alpha: Carer Hospsat 0.87, Carer Homesat 0.79). Most carers (77%) were satisfied with the care their relative or friend received while in hospital, but only 39% were satisfied with services after discharge. CONCLUSIONS--Carer satisfaction is an important outcome measure in stroke research. This study has shown that carers are dissatisfied with services after hospital discharge. Our questionnaire is valid, reliable, and sensitive and could be used to test interventions aimed at improving services.